2013
DOI: 10.1074/jbc.m112.445940
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Bacterial Oligosaccharyltransferase

Abstract: Background: N-Linked glycosylation is catalyzed by oligosaccharyltransferase (OST).Results: Specific amino acids in enzyme and acceptor substrate are identified as key determinants for substrate binding and turnover. Conclusion: Quantification of substrate binding and turnover reveal a delicate interplay between acceptor substrate, enzyme, and metal ion. Significance: The study represents the first quantitative analysis of substrate binding and turnover in N-linked glycosylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 57 publications
1
63
1
Order By: Relevance
“…A Cl PglB variant in which the native Q330/R331 residues were rationally replaced with DL glycosylated an AQNAT sequon as efficiently as the Cj PglB DL variant and retained highly efficient glycosylation of a DQNAT sequon. This is in stark contrast to studies where a Cl PglB R331A mutant generates only a very low level of AQNAT glycosylation and significantly reduces glycosylation of a DQNAT sequon 31 . Our results revealed that the adjacent Q330 (R327 in Cj PglB) residue plays an important role in regulating site selection along with R331.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…A Cl PglB variant in which the native Q330/R331 residues were rationally replaced with DL glycosylated an AQNAT sequon as efficiently as the Cj PglB DL variant and retained highly efficient glycosylation of a DQNAT sequon. This is in stark contrast to studies where a Cl PglB R331A mutant generates only a very low level of AQNAT glycosylation and significantly reduces glycosylation of a DQNAT sequon 31 . Our results revealed that the adjacent Q330 (R327 in Cj PglB) residue plays an important role in regulating site selection along with R331.…”
Section: Discussioncontrasting
confidence: 86%
“…In stark contrast, the relaxation of our mutants was much more general and potentially more useful for glycoengineering as demonstrated by glycosylation of RNaseA at its native N-X-S/T acceptor site. Recent efforts to further relax the specificity of Cl PglB by swapping the charged residues between the bacterial OST and acceptor peptide resulted in no apparent glycosylation of an RQNAT sequon by Cl PglB R331D/E mutants in vivo 31 . Here, the application of glycoSNAP resulted in a unique instance of charge inversion involving R327 of Cj PglB, where 3 of the 5 sequons most efficiently glycosylated by the DL variant contained Arg in the −2 position.…”
Section: Discussionmentioning
confidence: 99%
“…This could result from NXT providing a more optimal conformation of the acceptor sequence, with increased nucleophilicity of the asparagine amide group [91]. Furthermore, kinetics studies have demonstrated that the eukaryotic oligosaccharyltransferase enzyme has a higher affinity for NXT sites compared to NXS [95,96]. NXT motifs are also positively selected for in adjacent sequons, and are more likely than NXS to be glycosylated in this setting [97].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the structural analysis of PglB from C. lari (PglB Cl ) with a bound substrate peptide, extensive bioinformatics and biochemical studies have provided insight into optimized peptide substrate determinants, 25 the corresponding peptide binding site and potential mechanistic models for asparagine glycosylation. 26 Additionally, computational approaches have been applied to predict the structure of the undecaprenol-diphosphate-heptasaccharide (Und-PP-heptasaccharide) in complex with PglB. 27 …”
Section: Introductionmentioning
confidence: 99%